The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/srep06851
|View full text |Cite
|
Sign up to set email alerts
|

Radiocesium contamination of greenlings (Hexagrammos otakii) off the coast of Fukushima

Abstract: We measured the radiocesium (134Cs and 137Cs) contamination of 236 greenlings (Hexagrammos otakii) off the coast of Fukushima Prefecture in Japan, following the accident at the Fukushima Daiichi Nuclear Power Plant in March 2011. The radiocesium concentrations of greenlings caught approximately 40 km south of the power plant were significantly higher than those of greenlings caught approximately 50 km north of the power plant. The radiocesium concentrations of greenlings caught in southern waters were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
(32 reference statements)
1
17
0
Order By: Relevance
“…As a consequence, radioactive Cs would be transferred to the higher trophic level not only via surrounding seawater but also by prey-predator interactions in the pelagic ecosystem. Shigenobu et al (2014) reported the radioactive Cs concentrations of fat greenling (Hexagrammos otakii) caught off the coast of Fukushima Prefecture, and reported two outlier specimens caught in August 2012 and May 2013 which had ambiguously high 137 Cs concentrations of more than 1000 Bq/kg-wet. Probability analysis indicated that the two outlier fat greenlings had migrated from the port of FNPP.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, radioactive Cs would be transferred to the higher trophic level not only via surrounding seawater but also by prey-predator interactions in the pelagic ecosystem. Shigenobu et al (2014) reported the radioactive Cs concentrations of fat greenling (Hexagrammos otakii) caught off the coast of Fukushima Prefecture, and reported two outlier specimens caught in August 2012 and May 2013 which had ambiguously high 137 Cs concentrations of more than 1000 Bq/kg-wet. Probability analysis indicated that the two outlier fat greenlings had migrated from the port of FNPP.…”
Section: Introductionmentioning
confidence: 99%
“…We selected those species somewhat subjectively. Sebastes cheni (Japanese white seaperch) and Hexagrammos otakii (fat greenling) are well known as highly contaminated demersal fish (7,9,18). Salvelinus leucomaenis leucomaenis and Anguilla japonica are highly contaminated freshwater and diadromous fish from our analysis.…”
Section: Resultsmentioning
confidence: 95%
“…Shigenobu et al . () estimated that the heavily contaminated individuals of fat greenling had absorbed much radiocesium within or close to the FNPP port over a certain period immediately after the accident before moving offshore. In addition, on 17 November 2013, 12400 Bq kg −1 w.w. of radiocesium was detected in the muscle‐tissue sample of a blackhead seabream collected approximately 30 km south of the FNPP (Fisheries Research Agency, ).…”
Section: Discussionmentioning
confidence: 99%
“…Off the coast of Fukushima Prefecture, samples of fat greenling (Hexagrammos otakii) caught on 1 August 2012 and 8 May 2013, for which radiocesium concentrations of 25800 Bq kg À1 w.w. and 1700 Bq kg À1 w.w., respectively, were detected in their muscle tissues (Tokyo Electric Power Corporation, 2012). Shigenobu et al (2014) estimated that the heavily contaminated individuals of fat greenling had absorbed much radiocesium within or close to the FNPP port over a certain period immediately after the accident before moving offshore. In addition, on 17 November 2013, 12400 Bq kg À1 w.w. of radiocesium was detected in the muscle-tissue sample of a blackhead seabream collected approximately 30 km south of the FNPP (Fisheries Research Agency, 2014).…”
Section: Discussionmentioning
confidence: 99%